Epidemiology of depression among displaced people: A systematic review and meta-analysis. (May 2022) - Bedaso, Asres; Duko, Bereket
Highlight: Globally, around 1 in 4 displaced people suffer from depression. Three in five internally displaced persons (IDPs), one in three refugees and asylum seekers and one in four migrants suffer from depression globally. Being female, non-partnered marital status, and low perceived social support were the most common determinants of depression among displaced people. Culturally fitting and targeted response from migrant/refugee host nations and their serving clinicians is necessary. Abstract: Introduction: Displaced people are prone to develop mental health problems due to resettlement in new environments, traumatic events and forced migration. Depression is a mental health problem repeatedly observed among displaced people such as refugees, migrants, asylum seekers and internally displaced persons (IDPs). Therefore, estimating the global pooled prevalence of depression as well as pinpointing its determinants may support policymakers and health care workers to mitigate the disease burden and improve the psychological well-being of displaced people. Methods: PubMed, EMBASE, CINAHIL, Psych-INFO, and SCOPUS databases were searched for English written relevant observational studies conducted between 1984 and 2020. The methodological quality of studies was assessed using the Newcastle Ottawa Scale (NOS). Heterogeneity across studies was checked using the Q- and I 2 test. Publication bias was checked by observing Funnel plot symmetry and using Egger's regression test. STATA 16 was used to combine studies using a random effect model. Results: Of the 4102 studies identified, 81 studies with an overall sample size of 53, 458 were included in the current systematic review and meta-analysis. The pooled prevalence estimate of depression among displaced people was 26.4% (95% CI; 22.2-31.1). Also, three in five IDPs, one in three refugees and asylum seekers and one in four migrants suffer from depression globally. Being female migrant [AOR: 2.46 95% CI: 1.79-3.13, I 2 =34.5%), non-partnered marital status [AOR: 2.29, 95% CI: 1.29-3.30, I 2 = 0.00%], and perceived low social support [AOR: 1.76, 95% CI: 1.00-2.52, I 2 =34.6%] were significant determinants of depression among displaced people. Conclusion: Overall, around 1 in 4 displaced people suffer from depression and exceed the prevalence of depression reported by community samples in different nations and demonstrate a need for culturally fitting and targeted responses from migrant/refugee host nations and their serving clinicians.